Essentials of Financial Management. - Laws, Jason. (Liverpool University Press, 2019)
A compact text delivering the key concepts of finance and financial markets expected on an introductory course in corporate finance. Including numerous real world exercises with spreadsheet solutions, this is a paperback edition of an Open Access e-textbook.